The effect of e-wallet adoption towards the SMES productivity: a conceptual view - Suzanira Zainia; Suzillah Sidek (Universiti Malaysia Sabah, 2024)
Norm living during pandemic has completely change the way consumers perceive ewallet. Businesses including SMEs has continued to offer using e-wallet as transaction method. This study aims to: (i) to determine the factors influenced e-wallet adoption among SMEs and (ii) to determine the impact of e-wallet adoption towards the organization’s productivity of SMEs. The past literature related with e-wallet adoption mostly focusing on the e-wallet user - the buyer in economic cycle. However, literatures on e-wallet adoption from the seller perception are limited. Hence, the theoretical frameworks build based on four variables from UTAUT with two additional variables for technology adoption. The potential outcome from this paper is performance expectancy, effort expectancy, social influence and facilitating condition have a positive relationship with the adoption while perceived risk and perceived cost shows a negative relationship. Meanwhile, the exogenous variable of organisation productivity has positively affected by e-wallet adoption. The results presented in this study will be used to discuss both the current and upcoming research trends. This work will, in the end, aid researchers in better understanding the development of e-wallet use, particularly as it relates to sellers' perspectives.